Analisis Ekspresi Karakter Komik Jepang Pada Genre Seinen - Mukti, Indra Awaludin; Kasmana, Kankan (Universitas Komputer Indonesia, 2024)
Manga utilizes character expressions to convey complex emotional narratives. This is especially true when text is limited or omitted, such as scenes in Takehiko Inoue's Vagabond manga. Miyamoto Musashi, the strong and masculine main character, has several expressions of holding back tears. Reflecting emotions are depicted through facial elements such as forehead, eyebrows and eyes. The research aims to analyze the character of Musashi holding back tears in volume 32. The method used consists of three, namely analysis of shading techniques, analysis of facial expressions and gesture analysis. Data collection through non-participant observation and literature study. The result is that the combination of visual techniques, facial expressions, and body gestures is able to bring to life the character's inner emotions in a strong and expressive manner. This research is useful in revealing the role of visual elements in strengthening emotional narratives and deepening characterization, as well as making a significant contribution to the study of visual works and comic media. Keywords: Character, Comic, Emotion, Expression, Visual